Global Development Finance 2005 : Mobilizing Finance and Managing Vulnerability, Volume 2. Summary and Country Tables - World Bank (2012)
This report is comprised of two volumes. Global Development Finance 2005 I: Analysis and Statistical Appendix addresses two key challenges in development finance: first, how to raise resources flowing to low-income countries, which are heavily constrained in their access to market-based finance. Second, how to manage the vulnerability inherent in developing countries' access to finance -- vulnerability stemming from changes in the global macro environment, as well as from shifting donor priorities (affecting aid and concessional finance) and changing debt dynamics in developing countries. Global Development Finance 2005 II: Summary and Country Tables includes a comprehensive set of tables of data for 136 countries that report under the World Bank Debtor Reporting System, as well as summary data for regions and income groups. It contains data on total external debt stocks and flows, aggregates, and key debt ratios, and provides a detailed, country-by-country picture of debt. Global Development Finance 2005 debt data are also available on CD-ROM and online, with more than 200 historical time series from 1970 to 2003 and country group estimates for 2004.